EP415/#978 The modified 5-item frailty index (MFI-5) is a predictor of postoperative complications in vulvar cancer: a national surgical quality improvement program (NSQIP) analysis. (4th December 2022) - Levine, Monica; Felix, Ashley; Meade, Caitlin; Chambers, Laura
Abstract : Objectives: Frailty is a known predictor of post-operative morbidity, but the impact in women with vulvar cancer is unknown. Our objective was to determine whether frailty is associated with postoperative morbidity following radical vulvectomy (RV). Methods: Using the National Surgical Quality Improvement Program (NSQIP) database, women who underwent RV from 2014–2020 were identified. Frailty was defined utilizing the modified Frailty Index (mFI-5) assessing diagnoses of congestive heart failure, chronic obstructive pulmonary disease, diabetes mellitus, hypertension requiring medication and partial/total functional dependence. Patients were categorized as non-frail (0–1) or frail (2+). Multivariable-adjusted logistic regression analyses were performed. Results: Of 886 women, 49.9% underwent RV alone, and 19.5% and 30.6% concurrent unilateral or bilateral inguinofemoral lymphadenectomy (IFLND), respectively. 24.5% had mFI ≥2 and were considered frail. Compared to non-frail women, frail women were more likely to have an unplanned readmission (7.8% vs 12.9%, p=0.02), wound disruption (4.2% vs. 8.3%, p=0.02), and deep surgical site infection (1.4% vs. 3.7%, p=0.04). On multivariable-adjusted models, frailty was a significant predictor for minor (OR=1.58, 95% CI= 1.09, 2.30) and any complications (OR= 1.46, 95% CI= 1.02, 2.08). Specifically, for RV with bilateral IFLND, frailty was significantly associated with major (OR= 2.13, 95% CI= 1.03, 4.40) and any complications (OR= 2.10, 95% CI= 1.14, 3.87). Conclusions: In this NSQIP analysis, one-quarter of women undergoing RV were considered frail. Notably, frailty was associated with increased post-operative complications, especially in women concurrently undergoing bilateral IFLND. Frailty screening prior to RV may assist in patient counseling and improve postoperative outcomes.